Simulating response of wheat to timing and depth of irrigation water in drip irrigation system using CERES-Wheat model - Dar, E.; Brar, A.; Mishra, S.; Singh, Karam (Elsvier, 2017)
Conventionally wheat is irrigated at 4–5 growth stages with an irrigation water depth of 7.5 cm (conventional irrigation practice, CP) in North-Western India, resulting in wastage of water. An alternate yield sustaining cum water saving irrigation strategy is required. So, an experiment was conducted during 2014–15 and 2015–16 in split plot design at Punjab Agricultural University, Ludhiana, keeping three irrigation timings [three irrigations at crown root initiation, booting and milking (CBM); four irrigations at crown root initiation, tillering, booting and milking (CTBM) and five irrigations at crown root initiation, tillering, booting, milking and dough (CTBMD)] in main plots and four irrigation depth [50 mm at each stage in 2 splits (2SP); 75 mm at each stage in 3 splits (3SP); 100 mm at each stage in 4 splits (4SP); 75 mm at each stage conventionally (CP)] in sub plots, replicated four times. Five irrigations at CTBMD recorded significantly higher grain yield than 4 and 3 irrigations at CTBM and CBM, respectively. Four splits of 100 mm produced significantly higher grain yield than 2, 3 splits and CP (in pooled data). Crop evapotranspiration (ETc) and grain yield reduced by 14.5 and 13.4% in CBM than CTBMD. The reduction in ETc from 4SP to 2SP was 7–23% (15% for pooled data) with the highest (347–406 and 328–396 mm) in 4SP and lowest (319–374 and 258–298) in 2SP during 2014–15 and 2015–16, respectively. Similarly, 10.4% grain yield was decreased when irrigation applied at CP instead of 4SP. Though grain yield in 2SP and CP was similar, but there was water saving of 33.3% in 2SP as compared to CP. Therefore, application of 50 mm of irrigation water with drip can be recommended as a yield sustaining and water saving strategy and application of 100 mm of irrigation water at five growth stages using drip as a yield enhancing practice. The DSSAT model performed well (indicated by high correlation coefficient as well as low RMSE and MAPE) in simulating the days to anthesis (RMSE = 2.06 and 4.96 days; MAPE = 1.5 and 4.4%) and maturity (RMSE = 3.83 and 4.52 days; MAPE = 2.03 and 2.43%), LAI (r = 0.89 and 0.92; RMSE = 0.37 and 0.47; MAPE = 8.10 and 9.50%), grain yield (r = 0.92 and 0.97; RMSE = 154.60 and 160.90 kg; MAPE = 2.80 and 2.80%), biological yield (r = 0.67 and 0.58, RMSE = 584.9 and 691.0 kg; MAPE = 4.40 and 5.10%) and crop evapotranspiration (r = 0.95 and 0.96; RMSE = 9.20 and 16.20 mm and MAPE = 2.30 and 4.20%) during 2014–15 and 2015–16, respectively.